(untitled) (Nigerian Journal of Technology, 2005)
Five evapotranspiration (Et) model-the penman, Blaney - Criddel, Thornthwaite, the Blaney –Morin-Nigeria, and the Jensen and Haise models – were analyzed for parameter sensitivity under Nigerian Climatic conditions. The sensitivity of each model to errors in any of its measured parameters (variables) was based on the relative error introduced by the parameter in the predicted Et at various perturbations of the parameter. Three levels of sensitivity, herein termed sensitivity, ratings, were established, namely: Highly Sensitive (Rating:1); Moderately sensitive’ (Rating:2); and ‘not too sensitive’(Rating: 3). The ratings were based on the amount of error in the measured parameter to introduce + 10% relative error in the predicted Et. The level of importance and the care required in the measurement of each parameter with respect to the model in which it occurs are therefore established.